The Immediate Effect of Medial Wedge Insole and Neoprene Brace on the Pain, Knee Valgus and Gait in Patients with Patellofemoral Pain Syndrome: Randomized Cross-Over Clinical Trial - Ameneh Abedian-Aval; Niloufar Fereshtenejad; Ebrahim Sadeghi-Demneh (Vesnu Publications, 2020)
Introduction: Patellofemoral pain syndrome (PFPS) is a common problem that particularly affects active young people. In these patients, dynamic knee valgus causes hip and knee kinematic changes. Therefore, the reduction of dynamic valgus angle is one of the rehabilitation strategies in people with PFPS. The objective of this study was to evaluate the immediate effect of a medial wedge insole and knee orthosis on the knee pain and knee movement during walking and squat on involved side in people with PFPS.Materials and Methods: 15 volunteers with PFPS participated in this crossover clinical study. All participants signed the consent form and then were evaluated in four random conditions (without orthosis, medial wedge, medial wedge in combination with knee brace, and knee brace). The kinematics and kinetics of the lower limb were studied during walking and single-leg squat. Data analysis was performed using repeated measures statistical analysis of variance (ANOVA).Results: The knee brace, knee brace with medial wedge, and medial wedge significantly reduced the pain of affected leg after single-leg squat (P = 0.001). The walking speed (P = 0.067) and dynamic knee valgus angle (P = 0.490) did not significantly change in four different modalities of intervention. The peak moment of the knee in frontal plane was significantly increased in three conditions [medial wedge (P = 0.001), knee brace (P = 0.008), and knee brace in combination with medial wedge (P = 0.033)] compared with the control condition.Conclusion: Use of medial wedge and neoprene knee brace can decrease pain and improve the biomechanical performance of people with PFPS. The use of these interventions can cause positive biomechanical effects on the lower limb.